Sistem Informasi Penggajian Berbasis Web Pada PT. Rudi Agung Agralaksana - Mutia, Cut; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2023)
Company Rudi Agung Agralaksana is a company engaged in palm oil, which produces products in the form of Crude Palm Oil (CPO), kernels, shells. These products are Half finished products that must be processed further in order to become products that are ready to be sold to the public. Where the utilization of payroll system technology in Company Rudi Agung Agralaksana is still not good, and has several obstacles such as the storage of different files every month makes financial admins become confused in the payroll and reporting system, Some obstacles also often occur such as misunderstandings between financial admins and employees, sometimes financial admins also often forget to cut employee salaries due to different salary files every month. The purpose of this research is to analyze and design Web-based payroll information systems at company Rudi Agung Agralaksana. From these problems, research is carried out to analyze and design payroll information systems based on WEB using the Prototype method. research is a designof web based Payroll Information System to facilitate the financial admin, personnel and leaders in managing and viewing payroll systems.